Extraction of Channel Length Independent Series Resistance for Deeply Scaled Metal-Oxide-Semiconductor Field-Effect Transistors - 马丽娟 纪小丽 陈原聪 夏好广 朱晨昕 郭强 闫锋 (Chinese physics letters, 2014)
The recently developed four Rsd extraction methods from a single device, involving the constant-mobility method,the direct Id Vgs method, the conductance method and the Y-tunctlon metnoa, are evaluatea on 32 nm n-channel metal-oxide-semiconductor field-effect transistors （nMOSFETs）. It is found that Rsd achieved from the constant- mobility method exhibits the channel length independent characteristics. The L-dependent Rsd extracted from the other three methods is proven to be associated with the gate-voltage-induced mobility degradation in the extraction procedures. Based on L-dependent behaviors of Rsd, a new method is proposed for accurate series resistance extraction on deeply scaled MOSFETs.